Fabrication of carbon nanomembranes by helium ion beam lithography - Zhang, Xianghui; Vieker, Henning; Beyer, André; Gölzhäuser, Armin (Beilstein Journal of Nanotechnology, 2014)
The irradiation-induced cross-linking of aromatic self-assembled monolayers (SAMs) is a universal method for the fabrication of ultrathin carbon nanomembranes (CNMs). Here we demonstrate the cross-linking of aromatic SAMs due to exposure to helium ions. The distinction of cross-linked from non-cross-linked regions in the SAM was facilitated by transferring the irradiated SAM to a new substrate, which allowed for an ex situ observation of the cross-linking process by helium ion microscopy (HIM). In this way, three growth regimes of cross-linked areas were identified: formation of nuclei, one-dimensional (1D) and two-dimensional (2D) growth. The evaluation of the corresponding HIM images revealed the dose-dependent coverage, i.e., the relative monolayer area, whose density of cross-links surpassed a certain threshold value, as a function of the exposure dose. A complete cross-linking of aromatic SAMs by He+ ion irradiation requires an exposure dose of about 850 µC/cm2, which is roughly 60 times smaller than the corresponding electron irradiation dose. Most likely, this is due to the energy distribution of secondary electrons shifted to lower energies, which results in a more efficient dissociative electron attachment (DEA) process.
Keywords: carbon nanomembranes; dissociative electron attachment; helium ion microscopy; ion beam-organic molecules interactions; self-assembled monolayers